Infixations and Morphological Structure in Makasae Language - Soares, Antonio Constantino (Abdul Media Literasi, 2025)
This study investigates the morphological complexity of the ML, focusing specifically on its system of infixation spoken primarily in Timor-Leste. The ML features are unique use of affixes, such as ‘tuli,’ ‘geri,’ ‘ta,’ and ‘tau,’ which significantly alter the meaning and grammatical structure of verbs. These infixes mark causality, reciprocity, aspect, and action completion. The research adopted a qualitative approach, utilizing elicitation and semi-structured interviews with two to four native speakers as the primary data collection methods. The study reveals systematic patterns in infix placement and its impact on verb meaning, such as transforming verbs into fatal actions, signaling attempted actions, or indicating mutual actions. The findings highlight ML's sophisticated verbal morphology and its potential contribution to Papuan linguistic typology. The study suggests further research into dialectal variations, as well as the development of resources for language preservation and teaching.